Trends in Late Mortality and Life Expectancy After Autologous Blood or Marrow Transplantation Over Three Decades: A BMTSS Report. Issue 18 (20th June 2022) - Bhatia, Smita; Dai, Chen; Landier, Wendy; Hageman, Lindsey; Wu, Jessica; Schlichting, Elizabeth; Siler, Arianna; Funk, Erin; Hicks, Jessica; Lim, Shawn; Balas, Nora; Bosworth, Alysia; et al.
Abstract : PURPOSE: We determined trends in life expectancy and cause-specific late mortality after autologous blood or marrow transplantation (BMT) performed over a 30-year period, using the BMT Survivor Study. METHODS: We constructed a cohort of 4, 702 individuals with hematologic neoplasms who lived ≥ 2 years after autologous BMT performed between 1981 and 2014 at three transplant centers. The end of follow-up was April 19, 2021. The primary exposure variable was autologous BMT performed in four eras: 1981-1999; 2000-2005; 2006-2010; and 2011-2014. Vital status and cause of death were obtained from National Death Index Plus program and Accurinct databases. RESULTS: The median age at BMT was 53 years (range, 0-78 years), 58.7% were male, 67.8% were non-Hispanic White, and 28.3% had undergone transplantation between 2011 and 2014. Autologous BMT recipients experienced a 7-year reduction in life expectancy. The adjusted hazard of 5-year all-cause mortality declined over the four eras (reference: 1981-1999; hazard ratio [HR]2000-2005 = 0.77; 95% CI, 0.62 to 0.94; HR2006-2010 = 0.64; 95% CI, 0.51 to 0.79; HR2011-2014 = 0.56; 95% CI, 0.45 to 0.71; P trend < .001), as did years of life lost (5.0 years to 1.6 years). The reduction in all-cause mortality was most pronounced among those transplanted for Hodgkin lymphoma or plasma cell dyscrasias, but was not observed among those transplanted for non-Hodgkin lymphoma or those conditioned with total-body irradiation. We also observed a decline in late deaths because of infection ( P trend < .0001; primarily for BMTs before 2006) and subsequent neoplasms ( P trend = .03; confined to decline in therapy-related myeloid neoplasm–related mortality) but not because of cardiovascular or renal disease. CONCLUSION: Late mortality among autologous BMT recipients has declined over a 30-year period. However, ongoing efforts are needed to mitigate development of infections, subsequent neoplasms, and cardiovascular and renal disease to further reduce late mortality. Abstract :